Efektifitas Zakat, Infak, dan Sedekah (ZIS) Produktif dalam Pengentasan Kemiskinan di Kota Banda Aceh - Arwady Arwady; M. shabri (Fakultas Ekonomi dan Bisnis UNSYIAH, 2021)
This study aims to analyze the effectiveness of productive Zakat, Infaq, and Alms (ZIS) in increasing the income of the poor Mustahiq in Banda Aceh City and to analyze the effect of productive Zakat, Infaq and Alms (ZIS), gender, education level, type of work, and the number of dependents on increasing the income of the poor Mustahiq in Banda Aceh City. Based on 100 questionnaires distributed to respondents, using the purposive sampling technique and analyzed using multiple linear regression models, the results showed that productive ZIS was very effective in increasing Mustahiq's income in Banda Aceh City and the productive ZIS variable had a positive and significant effect on increasing income of the poor, while other characteristic variables consisting of gender, education level, type of work, and number of dependents have no effect on increasing the income of the poor in Banda Aceh City. Keywords: Productive ZIS, Income of the Poor, Effectiveness.